A new species of deep-sea anglerfish, genus Himantolophus (Lophiiformes: Himantolophidae) from the Western South Pacific, with comments on the validity of H. pseudalbinares - Stewart, Andrew L.; Pietsch, Theodore W. (Zootaxa, 2010)
A new species of the deep-sea ceratioid anglerfish genus Himantolophus is described from a single specimen caught off the east coast of the North Island of New Zealand. A member of the Himantolophus cornifer-group, based on the absence of a posterior escal appendage, the new species is described and compared with the five previously recognized members of the group. Evidence is provided to confirm the validity of Himantolophus pseudalbinares, a species previously confused with H. albinares.